Rethinking Auditors’ Fraud Detection: An Integrative Systematic Literature Review - Saputra, Dian; Kusuma, Hadri; Urumsah, Dekar (Dinasti International Journal of Economics, Finance & Accounting, 2026)
Auditors’ ability to detect fraud is multidimensional, yet the literature remains fragmented across technical, cognitive, and contextual domains. This Systematic Literature Review (SLR) synthesizes 56 empirical and conceptual articles from Scopus and Web of Science to construct an integrative framework of fraud detection determinants. We identify five overarching themes: auditor competency and skills, technology and CAATs, psychological traits, heuristics and cognitive biases, and governance and organizational context. While technical competency and experience remain primary drivers, cognitive biases and environmental pressures frequently impair judgment. Furthermore, while modern audit technologies (e.g., AI and CAATs) offer significant potential to mitigate these limitations, their effectiveness depends heavily on behavioral factors and organizational support. This study provides actionable insights to enhance auditor training, refine the adoption of audit technology, and foster supportive governance.